Um projeto sistematizado: o silenciamento do povo índigena Iny-Karajá na consciência goiana durante a ditadura militar (1964-1985) - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
From the arrival of the Portuguese to the present day, the indigenous populations of Brazil have gone through an arduous odyssey in the struggle to defend their territories, in a historical process in which this very important living space is still a crucial element for the continuity of these peoples and their families. cultures. With the Civil-Military Dictatorship (1964-1985), the period chosen as a time frame, the predatory actions of the capitalist economy intensified, contributing to the countless gaps in the history of these people, especially in the state of Goiás, the space chosen for this research, whose The topic lacks documents and analyzes that demonstrate indigenous protagonism throughout this regime. In this sense, starting from qualitative research and based on historical-dialectical materialism, this dissertation aims to investigate, based on bibliographic and documentary analysis, the silencing of indigenous populations in Goiás during the dictatorial regime as a systematized and articulated project. They participated in established capitalist interests in a more systematic in the Cerrado of Goiás from the 1960s onwards, focusing on the Iny-Karajá indigenous ethnic group. This is expected to elucidate the impact of the capitalist economic mode of production on this indigenous group and on the perpetuity of their traditional way of life.
A Systematized project: the silence of the Iny-Karajá indigenous people in the consciouness of goiana during the military dictatoryship (1964-1985)
Keywords: Indígenas Iny-Karajá - Silenciamento - Goiás(Estado); Indígenas Iny-Karajá - Ditadura Militar - Goiás(Estado); Indigenous Iny-Karajá - Silencing - Goias(State); Indigenous Iny-Karajá - Military dictatorship - Goias(State); CIENCIAS HUMANAS::ANTROPOLOGIA; CIENCIAS HUMANAS::HISTORIA